2019
DOI: 10.33225/jbse/19.18.880
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Students’ Engagement With R-SPQ-2f of Learning Approach in Flipped Sustainable Science Course

Abstract: The students’ engagement was deemed significant to research due to the changing study structures from course-based to student-centered and competence-based in sustainable science higher education. Still, its change and coping strategies is considered as somewhat unfamiliar learning environment. Research examined students’ engagement to the learning approach of a flipped-classroom model for sustainable science course with the Revised Two-Factor Study Process Questionnaire (R-SPQ-2F). It assesses research propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 49 publications
5
34
1
6
Order By: Relevance
“…Thus, Sterling (2001) indicated that its requirements for sustainability science education were related with human's potential realization and economic, social and ecological interdependence as educational culture change. In the educational and cultural setting, the procedures and resolutions of teachings focus on empowering learners along with dexterities, standards, evidence and a thinking-method, which execute as sustainability transformation delegates ( Fadeeva and Mochizuki, 2010 ; Jeong et al., 2019a , Jeong et al., 2019b ; Thomas, 2009 ). Sustainability science education is connected with knowledge performing and comprising the sustainability education principles though a confident examination part can connect with its specific methodologies, capabilities, competences and scientific and practical abilities ( Bacelar-Nicolau et al., 2009 ; González-G ómez and Jeong, 2018 ; Leal Filho et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Sterling (2001) indicated that its requirements for sustainability science education were related with human's potential realization and economic, social and ecological interdependence as educational culture change. In the educational and cultural setting, the procedures and resolutions of teachings focus on empowering learners along with dexterities, standards, evidence and a thinking-method, which execute as sustainability transformation delegates ( Fadeeva and Mochizuki, 2010 ; Jeong et al., 2019a , Jeong et al., 2019b ; Thomas, 2009 ). Sustainability science education is connected with knowledge performing and comprising the sustainability education principles though a confident examination part can connect with its specific methodologies, capabilities, competences and scientific and practical abilities ( Bacelar-Nicolau et al., 2009 ; González-G ómez and Jeong, 2018 ; Leal Filho et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Engagement of students has been linked to positive learning outcomes [1,2]. Several factors influence students' engagement, such as emotional engagement, behavior, cognitive, or agentic elements [2][3][4][5]. One of the elements that can influence students' engagement is the level of studies and voluntarism.…”
Section: Introductionmentioning
confidence: 99%
“…En las escalas principales, los valores de enfoque profundo (DA) fueron superiores a los valores de enfoque superficial (SA) en todos los cursos y la diferencia superior a cero con solo 4 casos de estudiantes con valores SA superiores a DA (datos no mostrados). En general estos resultados concuerdan con los obtenidos en otros estudios donde los alumnos muestran un mayor enfoque profundo que superficial (Leung, Ginns and Kember, 2008;Emilia, Bloomfield and Rotem, 2012;Mogre and Amalba, 2014;Jeong et al, 2017). Los alumnos objeto de estudio pertenecen a una titulación de máster y se ha visto que la edad es un factor que influye en el enfoque de aprendizaje, mostrando los alumnos mayores enfoque más profundo que superficial (Zeegers, 2001;Richardson, 2013;Rubin et al, 2018).…”
Section: Resultados Y Discusiónunclassified
“…Estudios realizados tampoco encuentran diferencias relacionadas con el género en el enfoque de aprendizaje del estudiante, aunque en algunos casos sí ligado a la edad (Richardson, 2013;Jeong et al, 2017). La distribución de los alumnos en función de los valores obtenidos en DA y SA (Figura 1) muestra que igual número de alumnos mostraron valores superiores al DA medio e inferiores al SA medio que alumnos con valores opuestos (DA inferior a la media y SA superior a la media) y menos alumnos con enfoques intermedios al igual que en otros estudios (Jeong et al, 2017). Esto que puede indicar que los alumnos se implican en la asignatura con un enfoque profundo o no se implican mostrando un enfoque superficial, pero no son tan frecuentes enfoques intermedios.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation